PENERAPAN INTERAKSI MANUSIA DAN KOMPUTER PADA ANTARMUKA SISTEM INFORMASI AKADEMIK - Isnaeni Hamidah; Bangkit Indarmawan Nugroho; Sarif Surorejo (Program Studi Informatika Universitas Teknologi Sumbawa, 2023)
A systematic literature review (SLR) is a study conducted by collecting and examining relevant journals. This study uses the idea of human-computer interaction to provide design recommendations for an educational information system in STMIK Tegal. This work gave rise to the concept of Human Computer Interaction (HCI) which is used to describe SIA in STMIK Tegal but has not yet been implemented due to the incomplete effectiveness and efficiency of utility system functions. The authors recommendation is to design a web-based AIS focusing on the fundamental principles of HCI. HCI is the science that studies computer technologies that affect human work and activities. The goal of HCI is to make it easier for users to interact with their computers and get the feedback they want.